Work Motivation as a Mediator of the Relationship between Transformational Leadership, Organizational Culture, and Personnel Performance: Evidence from the Indonesian Navy - Tang, Sukiantono; Agung SNP, Jeffrey; Bawono, Arso; Aseanty, Deasy; Anggiani, Sarfilianty (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to determine the influence of transformational leadership and organizational culture on personnel performance with work motivation as a mediator. This study adopts a quantitative approach through a survey method to test the hypothesis regarding the relationship between transformational leadership, organizational culture, work motivation, and personnel performance. The results of the study indicate that transformational leadership does not influence personnel performance even through work motivation. However, organizational culture and work motivation positively influence personnel performance. Additionally, organizational culture positively influences personnel performance through work motivation. Recommendations for future research include expanding the variables that may influence performance, such as work environment, competence, or job satisfaction, to obtain a more comprehensive understanding.